KAJIAN LIVING QUR’AN TRADISI PEMBACAAN AYAT KURSI SEBAGAI TOLAK BALA DI PPTQ AL-HIDAYAH PLOSOKANDANG TULUNGAGUNG - Nur Widad Rahmawati; Rifqi As'adah al Laily (UIN Siber Syekh Nurjati Cirebon, 2023)
Living Qur'an is a study that discusses various forms of public response or reception to the Qur'an. One of these phenomena is the tradition of reciting Ayat Kursi that occurred at the Tahfidzul Qur'an Islamic Boarding School Al-Hidayah Plosokandang Tulungagung. This study aims to describe the meaning of the tradition of reading Ayat Kursi at PPTQ Al-Hidayah. This research is a field research with a qualitative descriptive method. This research uses analysis of social knowledge of Karl Manheim which divides into three kinds of meaning. First, the objective meaning of reading Ayat Kursi here is to train students to be istiqamah in practicing this practice and a form of students' obedience to their caregivers. Second, the expressive meaning of reading the Ayat Kursi has the same benefits and goals but with a different explanation, namely as self-protection. Third, the documentary meaning of this tradition is that the students are not aware that this includes reading the Qur'an which has become a culture. This study also discusses the transmission and transformation of the reading of Ayat Kursi. Living Qur’an merupakan sebuah kajian yang membahas mengenai berbagai bentuk respon atau resepsi masyarakat terhadap al-Qur’an. Salah satu bentuk resepsi tersebut adalah tradisi pembacaan Ayat Kursi yang terjadi di Pondok Pesantren Tahfidzul Qur’an Al-Hidayah Plosokandang Tulungagung. Penelitian ini bertujuan untuk mendeskripsikan praktik dan pemaknaan tradisi pembacaan Ayat Kursi di PPTQ Al-Hidayah. Penelitian ini merupakan penelitian lapangan (field research) dengan metode deskriptif-kualitatif. Penelitian ini menggunakan analisis pengetahuan sosial Karl Manheim yang membagi menjadi tiga macam makna. Pertama, makna objektif dari pembacaan Ayat Kursi di sini adalah untuk melatih diri santri agar istiqamah dalam mengamalkan amalan ini dan wujud kepatuhan santri terhadap pengasuh. Kedua, makna ekspresif dari pembacaan Ayat Kursi ini memilliki manfaat dan tujuan yang sama tetapi dengan penjelasan yang berbeda yaitu sebagai pelindung diri. Ketiga, makna dokumenter dari tradisi ini bahwa para santri tidak sadar bahwa ini termasuk pembacaan al-Qur’an yang sudah menjadi budaya.